IKM dalam P5 Produk Herbal Halalan Toyyiban dengan Memanfaatkan Taman Sekolah - Muryati, Jamilah; Hilmizen, Naufal; Munandar, Aris; Koswara, Endang (VISA: Journal of Vision and Ideas, 2024)
This Community Service (PKM) was carried out because there are digitalization problems in this technological era. All office work, including teachers and students, use computers and cellphones for quite a long time, resulting in eye fatigue. The method used is counseling. The school garden data source is then distilled to obtain hydrosol water in the form of eye drops and face mist. To make eye drops, you can combine distilled betel leaves, kecombrang flowers and jasmine flowers. Meanwhile, to make face mist, you can combine distilled betel leaves, kecombrang flowers, ylang-ylang flowers and bidara leaves.